Experimental synthesis and density functional theory investigation of radiation tolerance of Zr(Al–,Si)C MAX phases - Zapata-Solvas,E; Christopoulos,SRG; Ni,N; Parfitt,DC; Horlait,D; Fitzpatrick,ME; Chroneos,A; Lee,WE (Journal of the American Ceramic Society, 2017)
Synthesis, characterisation and density functional theory calculations have been combined to examine the formation of the Zr3(Al1–xSix)C2 quaternary MAX phases and the intrinsic defect processes in Zr3AlC2 and Zr3SiC2. The MAX phase family is extended by demonstrating that Zr3(Al1–xSix)C2, and particularly compositions with x ≈ 0.1, can be formed leading here to a yield of 59 wt.%. It has been found that Zr3AlC2 – and by extension Zr3(Al1–xSix)C2 – formation rates benefit from the presence of traces of Si in the reactant mix, presumably through the in situ formation of ZrySiz phase(s) acting as a nucleation substrate for the MAX phase. To investigate the radiation tolerance of Zr3(Al1–xSix)C2 we have also considered the intrinsic defect properties of the end members. Aelement Frenkel reaction for both Zr3AlC2 (1.71 eV) and Zr3SiC2 (1.41 eV) phases are the lowest energy defect reactions. For comparison we consider the defect processes in Ti3AlC2 and Ti3SiC2 phases. It is concluded that Zr3AlC2 and Ti3AlC2 MAX phases are more radiation tolerant than Zr3SiC2 and Ti3SiC2 respectively. Their applicability as cladding materials for nuclear fuel is discussed.